Training facilitated by interinstitutional collaboration and telemedicine: an alternative for improving results in the placenta accreta spectrum - Albaro José Nieto-Calvache, MD; José Miguel Palacios-Jaraquemada, MD, PhD; Lina María Vergara-Galliadi, MD; Alejandro Solo Nieto-Calvache, MD; Maria Andrea Zambrano, MD; Juan Manuel Burgos-Luna, MD (Elsevier, 2021)
Placenta accreta spectrum is a severe condition that requires trained, interdisciplinary group intervention. However, achieving the level of training that is required is difficult without academic programs or hospitals dedicated to teaching the necessary skills to deal with placenta accreta spectrum. We describe an interinstitutional collaboration process focused on improving placenta accreta spectrum treatment, which is facilitated by telemedicine. Lastly, we propose a replicable model for other centers.This was a retrospective, descriptive study that included placenta accreta spectrum patients treated over a 10-year period in a low-middle income country hospital (local hospital). We evaluated the clinical results and impact of interinstitutional collaboration with a placenta accreta spectrum expert group at another low-middle income country hospital. Virtual strategies of continuous communication between the local hospital and expert group were used, such as telemedicine, teleradiology, and telepresence during surgeries.A total of 89 placenta accreta spectrum patients were included. We observed a progressive improvement in the clinical outcomes (intraoperative bleeding, transfusion frequency, postoperative length of stay, and frequency of complications) as the fixed interdisciplinary group at the local hospital gained experience by treating more cases.Interinstitutional collaboration (through telemedicine and remote supervision) and placenta accreta spectrum team formation were the 2 factors associated with the best outcomes in the most recent years of observation. Thus, ongoing placenta accreta spectrum team training, facilitated by interinstitutional collaboration and telemedicine, is a valid strategy for improving the clinical outcomes in placenta accreta spectrum.